The use of mechanical interlock in dental prosthesis - Abdul Kadir, Mohammed Rafiq; Osman, K.; Zainuddin, A. I. (Springer Berlin Heidelberg, 2008)
Good long term outcomes in prosthetic dentistry depends on the stability of its abutment-implant construct. One of the abutment designs normally used is a cylindrical taper where interference fit is achieved on large contact pressure and frictional resistance at the interface. Other designs include the screw and a combination of screw and taper. The stability of the implant body relative to the bone is also crucial because inadequate fixation would prevent bone integration. This study analysed a concept design where the abutment is locked mechanically once inserted into the dental implant body. Non-linear finite element contact analysis was carried out on the new design, as well as on a design based on a simple taper for comparison. Three dimensional model of the mandible was reconstructed from CT dataset and a section of the mandible was chosen for analysis. Pressure was applied on the top surface of the abutment simulating the normal biting force. Results showed that the mechanical interlock design was 5 times more stable than the simple taper design. However, the threshold limit for osseointegration was not exceeded for both implants. Stresses exerted on the distal region of the abutment for the taper design was an order of magnitude higher than the one found on the mechanical interlock.